Printability of gas atomized Mo-Si-B powders by laser metal deposition. (January 2019) - Schmelzer, J.; Rittinghaus, S.-K.; Weisheit, A.; Stobik, M.; Paulus, J.; Gruber, K.; Wessel, E.; Heinze, C.; Krüger, M.
Abstract: Mo-Si-B alloys, as a more and more frequently considered high-temperature material, face the challenge of machining complex shapes. In the present work, the feasibility of printing pre-alloyed Mo-Si-B powder materials via laser metal deposition (LMD) process was firstly demonstrated. Mo-Si-B powder was manufactured via gas atomization (GA) process out of solid raw materials meeting the requirements for additive manufacturing (AM) regarding flowability and particle size. Investigations of the powder particles after GA and detailed analyses of the printability and microstructural evolution of the multi-phase Moss -Mo3 Si-Mo5 SiB2 built are presented. As a result, distinct zones resulting from the layer-wise LMD process were observed next to a microstructure of primarily solidified Moss phases embedded in fine dispersed eutectic regions. The hardness of the LMD processed material is shown to be comparable with Mo-Si-B alloys produced by ingot metallurgy (IM). Highlights: Mo-Si-B powder was successfully produced by gas atomization out of raw materials. Flowability and particle size meet the requirements for additive manufacturing. Printing via laser metal deposition (LMD) was successfully conducted. Multi-phase Moss -Mo3 Si-Mo5 SiB2 builts are characterized by SEM and EBSD.